Apparent protein and energy digestibility and amino acid availability of corn and co-products in extruded diets for nile tilapia, oreochromis niloticus - Oliveira Vidal, Luiz Vitor; Xavier, Tadeu Orlandi; Michelato, Mariana; Martins, Elias Nunes; Pezzato, Luiz Edivaldo [UNESP]; Furuya, Wilson Massamitu (Wiley-Blackwell, 2015)
We assessed the nutritional value of corn in extruded diets for Nile tilapia, Oreochromis niloticus, by determining the apparent digestibility coefficients of dry matter, crude protein, and gross energy, and by measuring the apparent availability coefficients (AACs) of essential and non-essential amino acids (AAs) in several corn-based diets. We fed 180 juvenile Nile tilapia a reference diet containing 325.8g/kg crude protein and 4613kcal/kg gross energy or a test diet containing a 70:30 mixture of the reference diet and a test ingredient (whole corn, corn germ, corn germ meal, corn gluten feed, or corn gluten meal). The apparent digestibility coefficients ranged from 56.3 to 96.6% (dry matter), 89.4 to 96.8% (crude protein), and 59.0 to 95.4% (gross energy). The AACs of all AAs exceeded 80% for all diets and were >90% for corn gluten meal. All ingredients showed high levels of apparent digestibility for crude protein and high AACs of AAs. Diets based on whole corn or corn gluten meal showed higher digestibility values for dry matter and gross energy, suggesting that they are preferable choices for Nile tilapia.